Efficacy and safety of the biosimilar denosumab candidate (Arylia) compared to the reference product (Prolia®) in postmenopausal osteoporosis: a phase III, randomized, two-armed, double-blind, parallel, active-controlled, and noninferiority clinical trial - Ahmadreza Jamshidi; Mahdi Vojdanian; Mohsen Soroush; Mahmoud Akbarian; Mehrdad Aghaei; Asghar Hajiabbasi; Zahra Mirfeizi; Alireza Khabbazi; Gholamhosein Alishiri; Anousheh Haghighi; Ahmad Salimzadeh; Hadi Karimzadeh; et al. (Arthritis Research & Therapy, 2022)
Abstract Background/objective Osteoporosis is a global health concern with an increasing prevalence worldwide. Denosumab is an antiresoptive agent that has been demonstrated to be effective and safe in osteoporotic patients. This study aimed to compare the efficacy and safety of the biosimilar denosumab candidate (Arylia) to the originator product (Prolia®) in postmenopausal osteoporotic patients. Methods In this randomized, double-blind, active-controlled, noninferiority trial, postmenopausal osteoporotic patients received 60 mg of subcutaneous Arylia or Prolia® at months 0, 6, and 12 and were followed up for 18 months. The primary endpoint was the noninferiority of the biosimilar product to the reference product in the percentage change of bone mineral density (BMD) in 18 months at the lumbar spine (L1-L4), total hip, and femoral neck. The secondary endpoints were safety assessment, the incidence of new vertebral fractures, and the trend of bone turnover markers (BTMs). Results A total of 190 patients were randomized to receive either biosimilar (n = 95) or reference (n = 95) denosumab. In the per-protocol (PP) analysis, the lower limits of the 95% two-sided confidence intervals of the difference between Arylia and Prolia® in increasing BMD were greater than the predetermined noninferiority margin of − 1.78 at the lumbar spine, total hip, and femoral neck sites (mean differences [95% CIs] of 0.39 [− 1.34 to 2.11], 0.04 [− 1.61 to 1.69], and 0.41 [− 1.58 to 2.40], respectively). The two products were also comparable in terms of safety, new vertebral fractures, and trend of BTMs. Conclusion The efficacy of the biosimilar denosumab was shown to be noninferior to that of the reference denosumab, with a comparable safety profile at 18 months. Trial registration ClinicalTrials.gov, NCT03293108 ; Registration date: 2017–09-19.